On the significance of the employee status and of the personal scope of labour law regulation - Jakob, Nóra I (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The essay focuses on the relevance of the labour law regulation’s personal scope, what the holistic approach of employee status and its social part mean. There have been discussions in the European Union to which circle of working people shall the protection system of labour law apply, and how the security of employees can be guaranteed under the pressure of flexibility. The debates have been inspired by a changed economic and social environment in the XXth centrury. The essay presents the influence of the changing economic and social environment in the concept of employee status, and more closer in the Hungarian labour law regulation. The decision who is acknowledged to be an employee is made by the legislator. By making this decision the labour law regulation shows a tendency of withdrawal and moving forward in the last decades. The change of employment contract develops at the same time with the expansion of personal scope in Europe and shows a great variety. The legislation, judicial practice, legal practice and the collective bargaining influence the expansion of protection under labour law. The changes of personal scope in the Labour Code of 1992 and 2012 are presented, how it is extended and in which direction. The personal scope is also applied to link the public and private sector by finding a common focal point: the characteristics of emplyoment. While coping with the employment relations on the labour market and trying to fit into the self-employed – emplolyee-like person – employee categories, it is suggested to exceed the contractual framework by means of abstraction and using the concept of personal work relations. Employee status has social part; therefore the essay describes the social consequences of being employee and its relation to the employee status.